Low loading of P modified Rh nanoparticles encapsulated in N, P-doped carbon for boosted and pH-universal hydrogen evolution reaction. (19th January 2022) - Bi, Junlu; Zhai, Xuejun; Liu, Guishan; Chi, Jing-Qi; Wang, Xuanyi; Chen, Shaojin; Xiao, Zhenyu; Wang, Lei
Abstract: Searching for highly efficient and Pt-free electrocatalysts with comparable hydrogen evolution reaction (HER) activities to the benchmark Pt/C catalyst is highly demanded for developing renewable water electrolysis system but still remains challenging. In the current work, low loading of P modified ultrafine Rh nanoparticles encapsulated in N, P dual-doped carbon layers (Rh–P@NPC) have been prepared through a facile polymerization-impregnation followed by high-temperature pyrolysis process. Benefiting from the unique core-shell structural advantages and synergistic effect of Rh–P and NPC components, the resulting Rh–P@NPC catalyst not only exhibits remarkable electrocatalytic activity for HER in the whole pH range with a low overpotential of 31 mV, 65 mV, and 130 mV to drive a current density of 10 mA cm −2 in 0.5 M H2 SO4, 1.0 M KOH, and 1.0 M PBS, respectively, but also demonstrates high durability. It is worth to note that all these HER performances are on a par with commercial Pt/C catalysts for HER. This synthetic strategy provides possibility for the fabrication of carbon-based heterostructures with high catalytic activity and durability in harsh environments. Highlights: Low loading of P-doped Rh encapsulated in N, P-doped carbon layers are prepared. The Rh–P@NPC with high surface area with enable full expose of active species. The Rh–P@NPC exhibits excellent activity and stability for HER in the whole pH range. The P-doped Rh and NPC can synergistically enhance the HER activity and stability.